The Effect of Work Engagement and Competency on Employee Performance with Motivation as a Mediation Variable at Bp3mi Jakarta - Berliandra Haryono; Suharto; Dhistianti Meirahmawati (Indonesian Journal Economic Review (IJER), 2026)
This study aims to find empirical evidence of the influence of work engagement and competence on employee performance mediated by work motivation in employees at BP3MI Jakarta. This study uses a descriptive quantitative research design. With a population of 65 employees, the sample was determined using a total sampling technique so that the number of samples is the same as the population, namely 65 employees. Data were collected using a questionnaire, which was then processed using multiple linear regression analysis and path analysis using SPSS 25. The results of the study indicate that work engagement and competence have a positive and significant effect on employee performance, work motivation has a negative and insignificant effect on employee performance, work engagement has a positive and significant effect on work motivation, competence has no effect on work motivation, work engagement has an effect on employee performance through work motivation, and competence has no effect on employee performance through work motivation.